Análise dos efeitos de um plano educacional individualizado no desenvolvimento acadêmico e funcional de um aluno com transtorno do espectro do autismo - Pereira, Débora Mara (2014)
Given the paradigm of inclusive education, the presence of students with autism spectrum disorder in regular schools has become more significant in recent years. Studies have revealed, however, deficits in academic participation of these students in these settings. Among the factors contributing to this phenomenon include poor teacher training and the lack of strategies to promote curriculum access. The aim of this study was to develop an instrument that would promote academic inclusion of a student with autism through procedures that could simultaneously empower the teacher. In this perspective, the study aimed to analyze the effects of an Individualized Educational Plan (IEP), developed collaboratively with teachers, on the academic and functional development of a student with autism in an early childhood education setting. Data were collected in a private school located in the city of Natal in Rio Grande do Norte, in the course of the academic year 2012. In addition to the student with autism, one teacher, a specialized educator, and four teacher aides participated in the study. The research used a single subject quasi-experimental design (AB) as well as qualitative methods of data analysis. The study was conducted in three phases: characterization, baseline and intervention. The first comprised interviews with the child´s parents and teachers, as well as the identification of two routines focus of intervention. In the second phase, the amount of time the student spent engaged in the selected routines during baseline was analyzed. In the third phase, the researcher prepared, collaboratively with the teachers, an individualized educational plan (IEP) for the student. Finally, the IEP was implemented by the teachers. The results indicated qualitative and quantitative changes in student´s participation in academic and functional tasks after the intervention program